Adult Learners Motivation and Participation in Mylearningspace/Online Facilitation in National Open University of Nigeria. - Chukwuma, Nnenna Nancy (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
Participation in e-learning and online facilitation has been a daunting one with most learners having low morale seemingly as a result of poor motivation resulting in high level of attrition. The National Open University of Nigeria in order to reach out to the learners where ever they are, and to be technologically compliant in line with the best practice(s) in Open and Distance Learning system ODL, established the Mylearningspace platform with the (captivating inscription) (learn anytime, anywhere and anyplace). The learners’ participation in the Mylearningspace online facilitation has been dramatically low. It is against this backdrop that this paper seeks to examine adult learners’ motivation to participate in online facilitation through the MyLearningspace Platform established under the Learners Content Management Directorate of the National Open University of Nigeria. This study was guided by three research questions and three hypotheses. The paper also delved into the level of variation in the factors that either motivates or inhibits participation in online facilitation across gender. The study focused in two study centers in Lagos ie Lagos and McCarthy study centers. The study adopted descriptive survey research design. The population of the study was 1229 postgraduate students of NOUN out of which 301 students were sampled using the Taro Yamane sampling techniques. A 20 items questionnaire, Student Group Discussion and key Personality Interviews were used for gathering data. 301 copies of the questionnaire were distributed to the respondents out of which 297 were retrieved representing 98 percent. The research questions were analyzed using mean while the hypotheses were tested using t-test statistical tools. This study opined that adult learners were intrinsically motivated by instructional factors like the videos, facial contact/interactions with facilitators and the inherent zeal to get value for their money since most adult pay tuition from their own pockets. Again the study revealed that adult learners are also extrinsically motivated by the artistic design of the MyLearningspace platform, however extrinsic social factors motivating the learners are very low. The study also revealed that there is variation in the intrinsic instructional factors and extrinsic social factors motiving the learners across gender with the male adult learners been more motivated than their female counters. However, no variation was found in the artistic motivating factors. From the findings, it was concluded that there is relatively low motivation to use the Mylearningspace following the several inhibiting factors which are de-motivating. Based on the finding some of the recommendations were the provision of a robust learner support service, introductory course in ICT for all facilitators and students even as a prerequisite for recruitment/admission and the inclusion of real facilitators and students as part of the artistic design of the platform. Keywords: Open and Distance Learning (ODL), Adult learners, Motivation, Virtual, Synchronous, Asynchronous.